Hardy Spaces Associated to Schrödinger Operators on Product Spaces - Liang Song; Chaoqiang Tan (Journal of Function Spaces and Applications)
Let L=−Δ+V be a Schrödinger operator on ℝn, where V∈Lloc1(ℝn) is a nonnegative function on ℝn. In this article, we show that the Hardy spaces L on product spaces can be characterized in terms of the Lusin area integral, atomic decomposition, and maximal functions.